A case study of seed exchange networks and gene flow for barley (Hordeum vulgare subsp. vulgare) in Morocco - Jensen, H.R.; Belqadi, L.; Santis, P. de; Sadiki, M.; Jarvis, Devra I.; Schoen, D.J. (Springer, 2013)
Local patterns of seed regeneration and trade that occur outside the formal breeding sector (seed exchange networks) can have a strong influence on the genetic diversity and evolution of traditional crop varieties. Despite this, little is known about the extent to which seed exchange networks influence gene flow and genetic structure in traditional crop varieties. Here we study barley (Hordeum vulgare subsp. vulgare) in rural communes of Northern Morocco in 2008 and 2009. We quantified seed regeneration and exchange by farmers within the seed exchange network using structured interviews. Using SSR markers, we also quantified the neutral genetic diversity and structure of a complex of traditional varieties referred to as Beldi that is managed in this exchange network. The majority of farmers (>88 %) report cultivating Beldi. Most seeds of Beldi (7090 %) are maintained on-farm, while the remainder of seeds are obtained from local markets within the commune. Beldi has high genetic diversity and there is weak but significant genetic structure between communes (FST = 0.031). From SSR marker data there is evidence of a high level of gene flow between communes not reported in interviews. Seeds purchased in local markets likely represent seeds from a larger geographic region, leading to lower genetic structure among communes than expected based on the reported level of on-farm seed regeneration and local sourcing of seed. We discuss the implications of this seed exchange network for the conservation of traditional barley varieties in the study region.